2010
DOI: 10.1182/blood-2009-03-207563
|View full text |Cite|
|
Sign up to set email alerts
|

A phase II pilot study of tacrolimus/sirolimus GVHD prophylaxis for sibling donor hematopoietic stem cell transplantation using 3 conditioning regimens

Abstract: Combination tacrolimus and sirolimus graft-versus-host disease (GVHD) prophylaxis for allogeneic transplant in patients conditioned with a fractionated total body irradiation-based regimen has shown encouraging results. We studied this prophylaxis combination in 85 patients receiving a matched-sibling transplant conditioned with 3 different regimens: fludarabine-melphalan (n ‫؍‬ 46); total body irradiation-etoposide (n ‫؍‬ 28), and busulfan-cyclophosphamide (n ‫؍‬ 11). The conditioning regimens were completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
83
4
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 28 publications
5
83
4
1
Order By: Relevance
“…Unlike previously published evidence, 17,18,21,22 the combination of TAC and SIR did not appear to pose a higher risk of TA-TMA than with TAC/MTX±ATG. These results are in agreement with a retrospective study in which the incidence of TA-TMA in patients who were given TAC/SIR ± ATG was not significantly different from that in patients who received MTX with TAC or CYA (10.2% vs 4.3%), 23 or with those of a recently randomized phase II trial comparing TAC/SIR with TAC/MTX, 24 although the high incidence of TA-TMA reported in this latter trial (24.3% with TAC/SIR and 18.9% with TAC/MTX) should be noted.…”
Section: Baseline Characteristics Of Patientscontrasting
confidence: 86%
See 3 more Smart Citations
“…Unlike previously published evidence, 17,18,21,22 the combination of TAC and SIR did not appear to pose a higher risk of TA-TMA than with TAC/MTX±ATG. These results are in agreement with a retrospective study in which the incidence of TA-TMA in patients who were given TAC/SIR ± ATG was not significantly different from that in patients who received MTX with TAC or CYA (10.2% vs 4.3%), 23 or with those of a recently randomized phase II trial comparing TAC/SIR with TAC/MTX, 24 although the high incidence of TA-TMA reported in this latter trial (24.3% with TAC/SIR and 18.9% with TAC/MTX) should be noted.…”
Section: Baseline Characteristics Of Patientscontrasting
confidence: 86%
“…17,20,34 Our results show that, although levels above the upper normal limit of TAC (410 ng/mL in the TAC/SIR group or 415 ng/mL in the TAC/MTX group) are not associated with TA-TMA, very high levels (425 ng/mL) are an independent risk factor for TA-TMA development. Accordingly, correct drug management is crucial to prevent this complication, 17,20,34,35 especially among patients who suffer from compromised organ function, either due to acute GVHD or from transplantation-related morbidity. This close monitoring is especially critical in the first 4 months after transplantation, as 75% of patients with TA-TMA were diagnosed before day þ 110 post HSCT, mainly when patients have developed severe grade III-IV acute GVHD.…”
Section: Baseline Characteristics Of Patientsmentioning
confidence: 56%
See 2 more Smart Citations
“…Use of aprepitant in the context of SCT presents multiple opportunities for drug interactions. 3,4 Sirolimus and tacrolimus are immunosuppressive agents used for prevention of GVHD 5,6 that are also substrates for CYP3A4 isoenzyme and P-glycoprotein. 7,8 Drugs known to inhibit CYP3A4, such as aprepitant, have the potential to increase the bioavailability of these two agents, leading to overt toxicity.…”
mentioning
confidence: 99%